Ad-libitum drinking and performance during a 40-km cycling time trial in the heat. Issue 2 (17th February 2016) - Berkulo, Meriam A. R.; Bol, Susan; Levels, Koen; Lamberts, Robert P.; Daanen, Hein A. M.; Noakes, Timothy D.
Abstract: The aim of this study was to investigate if drinking ad-libitum can counteract potential negative effects of a hypohydrated start caused by fluid restriction during a 40-km time trial (TT) in the heat. Twelve trained males performed one 40-km cycling TT euhydrated (EU: no water during the TT) and two 40-km cycling TTs hypohydrated. During one hypohydrated trial no fluid was ingested (HYPO), during the other trial ad-libitum water ingestion was allowed (FLUID). Ambient temperature was 35.2 ± 0.2°C, relative humidity 51 ± 3% and airflow 7 m·s −1 . Body mass (BM) was determined at the start of the test, and before and after the TT. During the TT, power output, heart rate (HR), gastrointestinal temperature, mean skin temperature, rating of perceived exertion (RPE), thermal sensation, thermal comfort and thirst sensation were measured. Prior to the start of the TT, BM was 1.2% lower in HYPO and FLUID compared to EU. During the TT, BM loss in FLUID was lower compared to EU and HYPO (1.0 ± 0.8%, 2.7 ± 0.2% and 2.6 ± 0.3%, respectively). Hydration status had no effect on power output (EU: 223 ± 32 W, HYPO: 217 ± 39 W, FLUID: 224 ± 35 W), HR, gastrointestinal temperature, mean skin temperature, RPE, thermal sensation and thermal comfort. Thirst sensation was higher in HYPO than in EU and FLUID. It was concluded that hypohydration did not adversely affect performance during a 40-km cycling TT in the heat. Therefore, whether or not participants consumed fluid during exercise did not influence their TT performance.